PENGEMBANGAN DESTINASI WISATA BARU BERBASIS TAMAN BUNGA MATAHARI DI NAGARI AIE BATUMBUAK SOLOK YANG TERINTEGRASI KEGIATAN MAHASISWA KKN REGULER II TAHUN 2025 - Obel, Obel; Arifnur, Adi Arga; Fithri, Prima; Mishbah, Muhammad Muzakki; Auliya, Muhammad Sulthonx; Putri, Refa Rahmalida; Nazli, Raihan Naufal; Nabila, Putri; Islami, Fiqri Adilla; Efirmansyah, Rian (Jurnal Abdi Insani, 2025)
Nagari Aia Batumbuak, known as a cold, snow-free village, has a geographically suitable environment for cultivating various types of horticultural crops. These conditions are also excellent for the growth of various types of flowers. However, flower cultivation has so far been limited to hobbies and personal collections. Therefore, it has great potential to be developed into a new tourist destination to increase community income. One type of flower that can be used is the sunflower, which has wide adaptation to various conditions. The purpose of this activity is to develop a new tourist destination based on a sunflower garden in Nagari Aie Batumbuak Solok. The implementation of this activity will be integrated with the activities of the 2025 Regular KKN II students using socialization methods and direct field practice. The results obtained from the implementation of this activity are the availability of a location to be used for the development of a flower garden based on a site survey before the activity. The next activity will be a socialization of the potential for developing a flower garden in Nagari Aie Batumbuak and its potential to be used as a new tourist destination. The existing location is then designed according to the land conditions, then the placement of each element such as the location of beds, ditches, paths, and gazebos is arranged. The planting site was then cleared and cultivated according to the design. Afterward, a sunflower cultivation awareness campaign was conducted and a sunflower planting demonstration was held at the flower garden development site.